Relationship between parent–child attachment and depression among migrant children and left-behind children in China. (March 2022) - Shuang, M.; Yiqing, W.; Ling, J.; Guanzhen, O.; Jing, G.; Zhiyong, Q.; Xiaohua, W.
Abstract: Objectives: The objective of this study was to examine the relationship between parent–child attachment and depression in migrant children (MC), left-behind children (LBC) and non-left-behind children (NLBC) in China. Study design: This was a cross-sectional study. Methods: In total, 4294 children (4th to 9th grade) participated in this study, including 677 MC, 1411 LBC and 2206 NLBC from 17 different schools. Results: The results showed that (1) the prevalence of depression among MC (21.0%) and LBC (14.0%) was significantly higher than that among NLBC (10.8%); (2) the quality of parent–child attachment among MC was statistically significantly lower than among LBC and NLBC (the proportion of children whose father–child and mother–child attachments were both insecure was 55.4% among MC, 29.9% among LBC and 33.7% among NLBC); and (3) depression was affected by the interaction between the group of children and parent–child attachment; compared with NLBC whose parent–child attachments were both secure, the odds ratio of depression among MC whose parent–child attachments were both insecure was 7.39, which was significantly higher than LBC (5.34) and NLBC (4.86) whose parent–child attachments were both insecure. Conclusions: The prevalence of depression among MC and LBC was significantly higher than that among NLBC in China. The quality of parent–child attachment among MC was statistically significantly lower than that of LBC and NLBC. Secure attachment could reduce the risk of depression and insecure parent–child attachment increased the risk of depression. Depression was affected by the interaction between the group of children and parent–child attachment; migration was a significant risk factor associated with child depression.